2012
DOI: 10.1089/dna.2012.1719
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Single-Nucleotide Polymorphisms in Interleukin-12A and Risk of Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is characterized by airflow obstruction due to chronic bronchitis, emphysema, and/or disease of small airways. It has been reported that the genetic variation may play a role in the development and severity of COPD. The purpose of this study was to investigate whether singlenucleotide polymorphisms (SNP) in interleukin (IL)-12A and IL-12B were associated with COPD in a Chinese population. The IL-12A rs2243115 and IL-12B rs3212227 polymorphisms were genotyped by perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…In opposition to our results, the C allele was associated with higher risk of a wide range of diseases of immune dysregulation, including psoriasis, ankylosing spondylitis , nasopharyngeal , cervical and oesophageal cancers . However, no association was found between this variant and Chronic obstructive pulmonary disease (COPD) , pulmonary tuberculosis , Type I Diabetes, Acute coronary syndrome (ACS), pre‐eclampsia , psoriasis and IBD .…”
Section: Discussioncontrasting
confidence: 99%
“…In opposition to our results, the C allele was associated with higher risk of a wide range of diseases of immune dysregulation, including psoriasis, ankylosing spondylitis , nasopharyngeal , cervical and oesophageal cancers . However, no association was found between this variant and Chronic obstructive pulmonary disease (COPD) , pulmonary tuberculosis , Type I Diabetes, Acute coronary syndrome (ACS), pre‐eclampsia , psoriasis and IBD .…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, Sima and colleagues found that variant G allele carriers of IL12A rs2243115 were at higher risk of brain tumors compared with those carrying the wild-type T allele (34). Almost at the same time, Wang and colleagues provided evidence that the variant G allele at IL12A rs2243115 also contributes to higher risk of chronic obstructive pulmonary disease (35). To our knowledge, there is no other report examining the contribution of IL12A genotypes to oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[ 41 ] Additionally, Wang et al found that the frequencies of GT and GT+GG of IL-12A rs2243115 were significantly different from TT in chronic obstructive pulmonary disease (COPD), which further suggested that IL-12A rs2243115 polymorphism may contribute to genetic susceptibility to COPD. [ 42 ] Moreover, other studies indicated that the SNPs in IL-12A rs568404 might contribute to the risk of asthma and Graves’ disease in Chinese population; the TT genotype of IL-12A rs568408 was related to significantly decreased late-onset AD risk. [ 26 , 43 , 44 ] Since IL-12A was a subunit of IL-35 and recently IL-35 polymorphisms were explored to be related to the risk of CHD, [ 24 , 25 ] we aimed to explore the IL-35 polymorphisms on cognitive function in CHD patients.…”
Section: Discussionmentioning
confidence: 99%